PENGEMBANGAN PRODUK OBAT KUMUR KONSENTRAT DENGAN BAHAN AKTIF MINYAK ATSIRI DAUN SIRIH DAN DAUN CENGKEH - Dwi Setyaningsih; Siti Rahmi Nuabdi; Neli Muna (Jurnal Teknologi Industri Pertanian, 2019)
Tooth and mouth disease that is suffered by many people is the reason for the increasing usage of mouthwash. Mouthwash on the market contains alcohol which causes side effects. The purpose of this study is to develop mouthwash concentrate based on essential oil (betel leaves and cloves) that can be accepted by prospective consumers, and to analyze the eligibility criteria of the mouthwash industry investment. The respondents 100 peoples, ranging in 15 to 62 y.o including visitors at Botani Square Mall, Sempur Field, Bhayangkara Hospital Bogor, and IPB students. The research uses an action research approach including market identification, prototype design, research and development, product acceptance analysis and financial analysis. Some problems raised from respondent interview were the side-effects of product, no measuring cup attached, less practical package, and the price was not affordable. The research solution was a practical 30 mL prototype of bottle drops with measuring cap. The production cost was IDR 6,808 and selling price (based on customer willingness to buy) of IDR 20,000. The result also showed a good acceptance of product by most respondents. Based on financial analysis, this product was concluded as feasible for industrial implementation. Keywords: alcohol mouthwash, betel-clove essensial oils, financial analysis, mouthwash industry